Economic Impacts of Development Tourism Activities in Pangururan District, Samosir Regency Indonesia - Nanda Sofia, S.T (Talenta Publisher, 2021)
Abstract. The tourism sector dramatically affects the economic growth of an area, where tourism activities are expected to minimize poverty levels and manage local communities. However, the economic impact on tourism development activities is essential to note, addition to having a positive impact on tourism development activities it also has a negative impact. This study aims to see the extent of the impact that occurs in the Pangururan Regency in activities. The method used in this research is a qualitative study method through descriptive journals and literature studies. Economy development from tourism has a significant impact on regional tourism revenues. The results of this study are expected to measure the extent of the impact of economic development on the tourism sector. And moreover results are expected to help the government in developing tourism programs in Pangururan Samosir District which can increase tourists visiting both the tourism season and the semi-quiet season.